Hardware, software and peripherals : reference manual - Dela Cruz, Cecilio C.; Francisco, Ma. Teresa P.;Gatus, Marivic M.;Lansingan, Rolando R.;Manalo, Dhonnee R.;Martin, Revinson G. ([Place of publication not identifed] : [publisher not identified], 2004)
This book is intended for a one-semester course on Hardware, Software and Peripherals. It has written to help students learn the fundamentals of the aforementioned components and the installation procedure of each.
Chapter 1. The computer system -- Chapter 2. The system board -- Chapter 3. Microprocessors -- Chapter 4. Chipsets and RAM -- Chapter 5. Buses and Devices -- Chapter 6. BIOS Configuration -- Chapter 7. Hard disks fundamental -- Chapter 8. Software Installation -- Chapter 9. Trouble shooting and maintenance.
Keywords: HARDWARE -- SOFTWARE -- PERIPHERALS -- MANUAL